دور الطاقة النووية في تحقيق التنمية المستدامة - عطاء الله, توفيق; دمان ذبيح, عماد (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2021)
تعتبر الطاقة النووية من أهم اكتشافات القرن العشرين، وذلك بسبب طبيعتها المزدوجة فهي تستخدم في الأغراض العسكرية، و كذا في الأغراض السلمية، وعليه تتمحور الاشكالية حول دور الطاقة النووية في تحقيق التنمية المستدامة؟ و ماهي معيقات ذلك؟ وللإجابة على ذلك نتناول الاطار المفاهيمي للدراسة أولا ثم نتطرق الى دور و أهمية الطاقة النووية في تحقيق التنمية المستدامة، لنصل لدراسة عوائق التنمية المستدامة عن طريق الطاقة النووية، ومن أهم النتائج المتوصل اليها نجد الأهمية القصوى للطاقة النووية كونها شرط أساسي للتنمية المستدامة، وبالوقت نفسه خطورة استخداماتها العسكرية و تأثير ذلك على الأمن النووي العالمي. Nuclear energy is one of the most important discoveries of the twentieth century, and because of its dual nature, it is used for military purposes, as well as for peaceful purposes, and therefore the problem revolves around the role of nuclear energy in achieving sustainable development? What are the obstacles that? To answer this, we address the conceptual framework of the study first, then we address the role and importance of nuclear energy in achieving sustainable development, so that we can study the obstacles of sustainable development through nuclear energy, and among the most important results we find we find the ultimate importance of nuclear energy being a prerequisite for sustainable development, and at the same time a risk Their military uses and their impact on global nuclear security.